Deficiency of NLRP3 protects cerebral pericytes and attenuates Alzheimer’s pathology in tau-transgenic mice - Quan, Wenqiang; Decker, Yann; Luo, Qinghua; Chemla, Axel; Chang, Hsin-Fang; Li, Dong; Fassbender, Klaus; Liu, Yang (Frontiers in Cellular Neuroscience, 2024)
Activation of NLRP3-containing inflammasome, which is responsible for IL-1β maturation, has been shown to contribute to Alzheimer's disease (AD)-associated pathogenesis in both APP-and tau-transgenic mice. However, effects of NLRP3 on pericytes and subsequent cerebrovascular pathology in AD remain unknown. By cross-breeding human P301S tautransgenic mice and Nlrp3 knockout mice, and immunohistological and molecular biological analysis of brain tissues, we showed that deficiency of NLRP3: 1) reduced Iba-1, GFAP and AT8 antibody-immunoreactive phosphorylated tau-positive cells, but without significantly altering transcription of inflammatory genes, 2) preserved cerebral vasculature and pericyte coverage, and up-regulated Osteopontin gene transcription, and 3) improved cognitive function in tau-transgenic mice. To investigate how NLRP3 regulates pericyte activation and survival, we cultured pericytes from the brains of Nlrp3 knockout and wild-type mice and analyzed the cells by confocal microscopy and flow cytometry after immunofluorescent staining. NLRP3 deficiency prevented pericyte apoptosis. Treatment with IL-1β or H2O2 increased the expression of PDGFRβ in NLRP3-deficient pericytes, but decreased it in NLRP3 wild-type pericytes in a dose-dependent manner. Therefore, inhibition of NLRP3 may promote pericyte survival, improve cerebrovascular function, and attenuate AD pathology in the brains of tautransgenic mice. Our study supports NLRP3 as a novel therapeutic target for Alzheimer's patients.